2016
DOI: 10.1007/s00330-016-4426-z
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MRI for cervical spine clearance after blunt traumatic injury: a meta-analysis

Abstract: • There were 16 unstable injuries on follow-up MRI among 5286 patients. • The positive finding rate among obtunded patients was 0.12 %. • The positive finding rate among alert, awake patients was 0.72 %. • MRI has a high false-positive rate; its utility mandates further studies. • The use and role of "confirmatory" tests shows wide variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 50 publications
0
28
1
2
Order By: Relevance
“…For patients with suspected cervical spine injury, simple cervical radiography was changed to CT. One study reported that the accuracy of diagnosis through CT was significantly higher than that of diagnosis using simple cervical spine radiography [48]. Conflicting findings have been reported regarding whether CT is sufficient or MRI should be performed additionally [49][50][51].…”
Section: Evidence Review or Evidence Summarymentioning
confidence: 99%
“…For patients with suspected cervical spine injury, simple cervical radiography was changed to CT. One study reported that the accuracy of diagnosis through CT was significantly higher than that of diagnosis using simple cervical spine radiography [48]. Conflicting findings have been reported regarding whether CT is sufficient or MRI should be performed additionally [49][50][51].…”
Section: Evidence Review or Evidence Summarymentioning
confidence: 99%
“… 18 In children and adolescent patients, MRI is a good option to screen for any lesion without exposing the vulnerable patient to the radiation of a CT scan. Recent studies and meta-analyses have shown there is very little further benefit of MRI compared with CT in the detection of cervical spine injuries in the unconscious or awake patient, 19 , 20 although a missed injury rate of up to 5% of significant lesions has been reported for CT against MRI. 21 In addition, MRI is a good diagnostic tool to detect minor injuries such as vertebral bone bruise in adjacent levels.…”
Section: Diagnostic Work-up Of Cervical Spine Traumamentioning
confidence: 99%
“…This is especially true given the potentially devastating consequences of a missed unstable injury. 4,5 Clinicians are often concerned that persistent neck pain in the setting of negative CT may represent occult, unstable ligamentous injury. Therefore, many centers utilize magnetic resonance imaging (MRI) to evaluate for injury to the cervical spine discoligamentous complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, this too is controversial, as MRI has a high false-positive rate, potentially leading to unnecessary cervical collar treatment as well as delay of care while MRI is obtained. 1,2,4,6 To date, studies assessing the efficacy of MRI in blunt trauma patients with negative CT and persistent neck pain have yielded mixed results; [7][8][9][10][11][12][13][14][15] a recent metaanalysis concluded that insufficient data exist for determining whether MRI should be used in this population. 4 Given the paucity of useful data, we performed a retrospective review of neurologically intact blunt trauma patients presenting to our level Copyright 2020 by International Society for the Advancement of Spine Surgery.…”
Section: Introductionmentioning
confidence: 99%